HIV/AIDS and other sexually transmitted infections among military members of the armed forces of Serbia - Jadranin Željko; Šuljagić Vesna; Todorović Veljko; Trkuljić Miroljub; Vučetić Dušan (Vojnosanitetski Pregled)
Background/Aim. Military personnel is a population group at special risk of exposure to sexually transmitted diseases (STD). In peacetime, STD infection rates among service members are generally 2 to 5 times higher than among civilian population. In time of conflict, the differences can be 50 or more times greater. This study describes sexual behavior as a risk factor for STD in the Armed Forces of Serbia. Methods. The sample of 5 617 voluntary blood donors from the Armed Forces of Serbia gave blood and filled World Health Organization Questionnaire about sexual behavior within January 2007 - December 2008 period. The mandatory testing of voluntary blood donors was performed in the Institute of Transfusiology Military Medical Academy in Belgrade, by the specific immunoenzyme tests and polymerasa chain reaction tests for HIV, hepatitis B, C and syphilis. Statistical analysis of data was done using State for Windows 93, USA, 1996. Results. We identified 36 soldiers with some form of STDs. This study showed that 1 668 (29.7%) tested soldiers reported always using condoms, 1 725 (30.72%) almost always, 1 238 (20.04%) sometimes, 495 (8.81%) almost never and 490 (8.73%) never. Among the sample, 449 (7.99%) soldiers reported sexual contacts with partners with high risk of sexual behavior, whilst 22 (0.37%) of them reported homosexual and bisexual contacts. Conclusion. This study reported STDs found in voluntary blood donors among the service members of the Armed Forces of Serbia, but none of them was identified to be HIV positive. Soldiers with the most frequent risk behavior were reported to be those with inconsistent condom use. In the future, the STD Control and Prevention Program should be more intensively conducted among the members of the Armed Forces of Serbia.